Generation of erosion profile of through hole in electrochemical boring using a stepwise moving electrode. (20th April 2005) - Hocheng, H.; Kao, P.S.; Lin, S.C.
Electrochemical machining has been increasingly recognised for its micromachining applications. A process to erode a hole of hundreds of micronmetres on the metal surface using a moving electrode is investigated in the current paper. This study provides the prediction of the produced hole enlargement and taper under the applied machining conditions during the process. A computational model is presented to illustrate how the machined profile develops as the time elapses and the electrode gap changes. The analysis is based on the fundamental law of electrolysis and the mathematical integral over a tool. The effectiveness of the model is examined by experiments using several schemes of the electrode movement.